Lincoln, Neb., Rev. Ordinances pt. 2, ch. 14, art. 26, §§ 1, 3-4 (1895) - (:unkn) unknown (My University, 1895)
No person, except an officer of the law in the discharge of his duty, shall fire or discharge any gun, pistol, fowling-piece, or other fire-arm, within the corporate limits of the city of Lincoln. Also prohibited the carry and discharge of toy guns.
Keywords: DISCHARGE